From stable isotope ecology to forensic isotope ecology — Isotopes' tales. (July 2019) - Meier-Augenstein, Wolfram
Highlights: Review of applications of stable isotope ecology and forensic stable isotope ecology. Potential and caveats of isotopic analytical approaches to wildlife forensics are being discussed. Information is provided why differences in stable isotopic composition result in measureable differences in chemical and physical properties. Abstract: Stable isotope ecology and forensic isotope ecology are not only linked by name. More often than not, knowledge and insights gained through the former serve as a springboard for application focused work of the latter. This review aims to offer a glimpse into the fascinating world of both though with more emphasis on forensic isotope ecology. To this end a selection of past and recent published work is presented and discussed to highlight both potential and limitations of isotopic analytical approaches to the detection of illegal trade in plants and animals.